Management Strategies for Cardiac Fibromas in Early Childhood: Comparative Analysis of Surgical Outcomes and Natural History - Oleksii M. Datsko; Nadiya M. Rudenko; Oleksandr V. Doronin (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Cardiac fibromas (CFs) are rare primary cardiac tumors. Defining surgical indications for CF resection in early childhood represents a challenging clinical issue and varies substantially between centers. The optimal management strategy, particularly in infants and young children, requires further generalization of accumulated clinical experience.Aim. To analyze the experience of a single specialized center in managing children with CFs and to compare the outcomes of surgical treatment with the natural course of the disease.Materials and Methods. In this retrospective single-center study (2014–2023), 12 cases of CF in early childhood were analyzed: seven patients were managed conservatively, and five underwent surgical tumor resection.Results. The median age at diagnosis was 1.1 years. Asymptomatic presentation occurred in 58 % of children, arrhythmias in 33%, and signs of heart failure (HF) in 17 %. Fibromas were most commonly located in the interventricular septum (33 %), right ventricle (33 %), and left ventricle (25 %), and less frequently in the right atrium (8 %). In the observation group (median follow-up 3.6 years), an increase in absolute tumor area was noted, while the indexed area decreased (-0.94 cm²/m²/year); no deaths were recorded, and two children required antiarrhythmic therapy. In the surgical group, complications occurred in 60 % of patients (left ventricular dysfunction, ventricular septal defect, tumor recurrence, repeat surgery). Overall survival was 100 % in both groups.Conclusions. In early childhood, CFs tend to regress relatively as the child grows. In contrast, early radical surgery is frequently associated with postoperative complications. Therefore, a stratified management strategy appears optimal: urgent resection should be performed in cases of severe arrhythmia or hemodynamic obstruction, while delayed surgery is preferable for asymptomatic patients or those with medically controlled symptoms.